Chapter Introduction Households and peripheral financialization in Eastern and Southern Europe - Mikuš, Marek (Taylor & Francis, 2021)
The introduction opens by identifying issues in the scholarship on the financialization of households that the collection seeks to rectify: atheoretical and unclear conceptualizations of the household; its treatment as a "black box"; and the one-sided focus on Anglo-Saxon cores of the global economy. The second section presents the authors' approach to financialization in Eastern and Southern Europe, which combines the concept of peripheral financialization with an awareness of the wider semi-peripheral character of these regions. The third section reviews classical and recent debates about the concept of the household, especially in anthropology and feminist economics. The fourth section formulates the authors' conceptualization of the household as a micro-level social institution oriented to a characteristic set of activities and as the subject of multiple systems of knowledge, social norms and public discourse. The fifth section presents the state-of-the-art of scholarship on household financialization and, synthesizing the insights of the earlier sections, formulates a set of general arguments about transformations of households under financialization in general and in Eastern and Southern European semi-peripheries in particular. The introduction concludes with an outline of the collection.